Kerasionalan Penggunaan Obat Diare yang Disimpan di Rumah Tangga di Indonesia - Raini, Mariana; Gitawati, Retno; Rooslamiati, Indri (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2015)
Diarrhea is a major health problem in developing countries. WHO data showed diarrhea caused the death of 2.5 million people, 80% are children under five years old. Riskesdas 2013 stated the prevalence of diarrhea in Indonesia is 7%, whereas 12.2% of it are children under five years old. Self-medication is common and access for the medicine is easy. This analysis aims to assess the rational use of diarrhea medication stored in households. The rational drug used is associated with the mother's education level and household ownership quintile. This study design is cross sectional. The data was taken from Riskesdas 2013 namely type of medicines (data from block VI), mother’s education level data (from block IV) and economic status presented as household ownership quintile level (data from block IX). The result showed that the highest percentage of diarrhea drugs stored at household is adsorbents (40.4%), followed by antibiotic (22.4%) and traditional medicine (18.5%). Rationality of diarrhea medications stored in households is 74.7% and irrational (25.3)%). Wealthy people (quintiles 4 and 5) are 2.019 times more rational compared with the poor (quintiles 1, 2 and 3), while mothers with a good education (high school and above) are 1.944 times more rational in using medicine for diarrhea treatment compared with mothers with low education (below high school).